Sinergitas Konservasi Merak Hijau Guna Revitalisasi Kesenian Reog Ponorogo - Nency Arta Amanda; Indirra Yasmine Putri S; Della Ika Lutfiana; Kharisma Rizqykha A; Denny Oktavina Radianto (JOURNAL SAINS STUDENT RESEARCH, 2024)
The potential of the green peacock as a symbol of local wisdom can be integrated into Reog performances to increase the attractiveness of traditional art. This article was written with the aim of finding out the benefits of peacock feather conservation which is carried out as a form of preserving regional art, namely Reog Ponorogo. This peacock, which is thought to be extinct, is being preserved by the people of Ponorogo. Apart from conserving peacocks, the people of Ponorogo also preserve their art by producing their own peacock busts. The method for writing this article is to carry out descriptive data analysis by means of literature study. This research discusses the conservation of green peacock feathers in Ponorogo as a means of preserving Reog, so that it can be seen that the two are related to each other. This conservation provides benefits for the Indonesian people because it preserves regional arts, especially Ponorogo.